Rice seeds yield and quality according to fertilization - Santana, Edivado Sousa; Ramos, Lisandro da Luz; Feitoza, Hudson da Costa; Mielezrski, Fabio; medeiros, João Carlos (Comunicata Scientiae, 2017)
To obtain high seed quality, good fertilization practices are essential due to its influence not only on seed yield and weight, but also controlling the development of seedlings anomalies. Therefore, the aim of this study was to evaluate the effects of different forms of fertilization on yield and physiological quality of upland rice seeds. It was used nitrogen fertilization in coverage as urea and foliar fertilization with macro and micronutrients. The treatments consist of various sources and forms of fertilization, in a randomized block design, as follows: covering at tillering with N at 34 kg ha-1; covering at floral primordium with N at 34 kg ha-1; foliar fertilization at tillering; foliar fertilization in floral primordium; covering with N at 34 kg ha-1 in tillering and foliar fertilization in floral primordium; only basic fertilization and treatment without fertilization. The results showed that the application of nitrogen fertilizer with urea, at tillering and floral primordium at 34 kg ha-1 of N increased the production of rice seeds. In addition, coverage with urea and foliar fertilization containing macro and micronutrients increased rice seeds yield and physiological quality.